Low Frequency of Drug-Resistant virus did not Affect the Therapeutic Efficacy in Daclatasvir plus Asunaprevir Therapy in Patients with Chronic HCV Genotype-1 Infection. Issue 1 (January 2016) - Kinugasa, Hideaki; Ikeda, Fusao; Takaguchi, Kouichi; Mori, Chizuru; Matsubara, Takehiro; Shiraha, Hidenori; Takaki, Akinobu; Iwasaki, Yoshiaki; Toyooka, Shinichi; Yamamoto, Kazuhide
Background: The efficacy of a direct-acting antiviral agent (DAA) is compromised by the development of drug resistance. The associations between resistance-associated virus (RAV) and therapeutic outcomes have not been well-understood. Methods: A total of 30 patients with HCV genotype-1b were enrolled and treated for 24 weeks with asunaprevir (ASV) and daclatasvir (DCV). Viral sequences in non-structural (NS) regions 3 and 5A in serum and liver tissue before treatment were examined with direct sequencing, next-generation sequencing (NGS) and the PCR-invader method to evaluate the importance of drug-resistance in the prediction of the outcomes of ASV plus DCV therapy. Results: Of 30 patients (22 treatment-naive patients, 2 interferon-intolerant patients and 6 non-responders), 25 patients (83.3%) achieved sustained virological response (SVR) 24 weeks after the treatment. Viral breakthrough occurred in three treatment-naive patients and one non-responder. One treatment-naive patient experienced viral relapse. Among 25 patients without RAV, 24 obtained SVR, whereas 5 patients had RAV with a 1.3 to 88% frequency, resulting in various therapeutic outcomes. As for HCV compartments, similar RAVs were detected in serum and liver tissue for a patient obtaining SVR despite HCV NS5A Y93H and another developed viral breakthrough although no RAV was detected. Direct sequencing could not detect RAVs in low frequency (1.3 to 12%) for three of four patients. Conclusions: Low frequency of RAVs might not affect the outcomes of ASV plus DCV therapy. Deep sequencing and PCR-invader methods can detect clinically significant RAVs for ASV plus DCV therapy.